2018
DOI: 10.1007/s10792-018-0870-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal quantitative assessment of macula during therapy with fingolimod in relapsing–remitting multiple sclerosis

Abstract: In our cohort, therapy with fingolimod did not cause any change in CFT and TMV in MS patients during a 12-month follow-up independent of previous ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
3
8
1
Order By: Relevance
“…Among these, one of the most significant, in terms of the number of patients and duration of the follow-up, highlighted a higher rate of RNFL thinning in ON+ patients, as reported in our results. However, unlike our data, ON− patients presented statistically significant annual change rates [36].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Among these, one of the most significant, in terms of the number of patients and duration of the follow-up, highlighted a higher rate of RNFL thinning in ON+ patients, as reported in our results. However, unlike our data, ON− patients presented statistically significant annual change rates [36].…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the BCVA in the whole sample, in accordance with previous studies [15,36], we observed a stability and an improvement rate that was not clinically significant, being less than 10 ETDRS letters (2 lines) on average, which is considered the cutoff for this test.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, several studies reported a preserved macular structure and thickness over time in RR-MS patients treated with fingolimod (Fruschelli et al, 2019;d'Ambrosio et al, 2020). Worthy of note, although macular edema is reported as a side effect of fingolimod administration with an incidence of 0.3-1.2% (Nolan et al, 2013), two studies evidenced that RR-MS patients treated with fingolimod did not show any case of macular edema (Fruschelli et al, 2019;Rossi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the TRANSFORMS trial, ME was diagnosed in two out of the 429 patients treated with the approved FNG dosage of 0.5 mg (0.5%) [1]. In a longitudinal OCT study, over 12 months treatment with FNG, no cases of FNG- [10]. Probably due to the effect of FNG on its main target, the sphingosine-1phosphate (S1P) receptor, also expressed on the endothelium of the blood-retina barrier, an increase in TMV less than 0.05 mm 3 has been reported 3-5 months after starting FNG in RRMS patients [4,5].…”
Section: Discussionmentioning
confidence: 99%